PELATIHAN PEMBUATAN VIRGIN COCONUT OIL DAN KECAP MANIS DARI KELAPA DI KECAMATAN MOROTAI JAYA KABUPATEN PULAU MOROTAI - Yuliana Wattimena, Anna; Ivonne Nendissa, Jeanne; G. I. Kembauw, Marthina (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
Coconut is a commodity that has a high economic value if it is used every part of it into a type of derivative product for sale. Assistance in making VCO and soy sauce is one of the community service activities from the Ambon Community Training Center with the Pattimura University Innovation Center. This activity was carried out as a way to provide solutions for the people of Morotai Jaya with the hope that it could help increase the economic value of coconut and increase people's income on a household scale. The main purpose of community service activities with the theme "Training for Superior Products in Rural Areas" is to provide counseling and training to the community about the use of coconut fruit as raw material for making VCO and coconut water soy sauce to be used as entrepreneurial opportunities for rural communities in Morotai Jaya sub-district. The method used in this service is counseling and training on making VCO and coconut soy sauce in a simple way. The results of this activity showed that the 45 minute treatment resulted in high VCO. The practice of processing VCO and soy sauce has succeeded in providing experience and at the same time skills in processing superior products in rural areas.